(untitled) (Research, Society and Development, 2021)
The objective of this work was to identify the most suitable conditions for the evaluation of the germination test in corn seeds through the use of different substrates. Two tests were carried out for the development of the work. In test 1, the hybrid Morgan 30A37 PWV was used in a factorial scheme of 5 substrates with 8 chemical treatments. The seeds were treated industrially with the following insecticides: Inside FS, Inside FS + Maestro FS, Maestro FS, Poncho, Inside FS + BioCoat Corn, Inside FS + Maestro FS + BioCoat Corn and Maestro FS + BioCoat Corn. For test 2, the hybrid used was the FS533 PWV in a factorial scheme of 5 substrates and 5 treatments, in which the seeds received the industrial treatment with the insecticides: Inside FS, Inside FS + Maestro FS, Maestro FS and Poncho. Both tests were submitted to two temperatures (20°C and 25°C) and five substrates (germitest® paper; germitest® paper + sand; germitest® paper + soil; germitest® paper + coal and brown paper). The most suitable substrates for installing the germination test in chemically treated corn seeds were brown pepper and germitest® + charcoal. And the temperature of 20°C is the one that allows the most uniform and rapid development of normal seedlings in the germination test in treated hybrid corn seeds.